Distributed leadership within the context of a semi government: the Employees Trust Fund of Brunei Darussalam - Maz Adanan, MA (2010)
Leadership is a complex subject which has always evolved over time. Literature on leadership has always seen it from an individualistic point of view in which leaders play a sole role in leading. Nowadays organizations whether public or private have also evolved due to the changing environment. They have become more complex in nature as well, due to globalization for example. Classically the very essence of leadership is the top to down leading but nowadays those at the bottom level are also required to practice leadership as well. This has changed the way leadership has been seen and thus results in newer forms of leadership. Distributed leadership is nowadays the new in thing within the leadership literature. Other familiar names that distributed leadership have that we may have heard of are like shared leadership and collaborative leadership. Distributed leadership moves beyond merely the individualistic form and takes a more group or team like form of leadership. This dissertation will try to pick up on the rise of distributed leadership from within the leadership literature. Recently this concept within the realm of leadership literature is being seen as effective with regards to performance and organizational changes amongst the public and private sector scenario. This dissertation on the other hand will try to make a qualitative analysis from a different angle that is from the semi government perspective within the South East Asian context. Due to the very challenging nature of the organization with respect to changes and performances, the role being played by traditional leadership practices is seen to be less effective hence forth the potentiality of the usage of distributed leadership to ensure success at every level ensures the high level of performance within the organization is maintained.